2011
DOI: 10.2463/mrms.10.219
|View full text |Cite
|
Sign up to set email alerts
|

MR Contrast in Mouse Lymph Nodes with Subcutaneous Administration of Iron Oxide Particles: Size Dependency

Abstract: Purpose: We investigated the spatiotemporal changes in signal in draining lymph nodes of mice to ascertain the size-dependent eŠects of variously sized particles of iron oxide used to enhance magnetic resonance (MR) lymphography.Materials and Methods: We injected iron oxide particles of 50-, 100-, 200-, or 1,000-nm diameter into the footpads of individual mice and obtained sequential MR images of the popliteal and inguinal lymph nodes with 11.7 tesla up to 6 weeks after particle administration.Results: Up to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…To overcome inherent limitations in the signal to noise ratio (SNR) of conventional in vivo MRI, a stronger magnetic field can be applied. In addition, super-paramagnetic nanoparticles of iron oxide (SPIO), a contrast agent for MRI, improves MRI contrast to noise ratio (CNR) and detectability in the stronger magnetic fields by shortening the T 2 /T 2 * relaxation time, further advancing MRI application in cell imaging and tracking789. Combining high-magnetic-field strength with high-sensitivity radio-frequency (RF) coils and optimal contrast agents enables the visualisation of cell populations and molecular events in vivo in both animals and humans910.…”
mentioning
confidence: 99%
“…To overcome inherent limitations in the signal to noise ratio (SNR) of conventional in vivo MRI, a stronger magnetic field can be applied. In addition, super-paramagnetic nanoparticles of iron oxide (SPIO), a contrast agent for MRI, improves MRI contrast to noise ratio (CNR) and detectability in the stronger magnetic fields by shortening the T 2 /T 2 * relaxation time, further advancing MRI application in cell imaging and tracking789. Combining high-magnetic-field strength with high-sensitivity radio-frequency (RF) coils and optimal contrast agents enables the visualisation of cell populations and molecular events in vivo in both animals and humans910.…”
mentioning
confidence: 99%
“…The purpose of these studies was to optimize tracer uptake in the SLNs to facilitate preoperative localization with MRI, rather than intraoperative detection. Mori et al 30 used 50 nm, 100 nm, 200 nm, and 1,000 nm-sized particles and concluded that particles of 200 nm and larger are not suitable in view of lack of uptake within 24 hours. Iida et al 28 compared the performance of 4 nm, 8 nm, and 20 nm citrate-coated nanoparticles and concluded that the 20 nm particles were best retained in the SLNs and accumulated in the highest concentration.…”
mentioning
confidence: 99%
“…[28][29][30] Tracers with particle sizes ranging from 4 to 1,000 nm were used in these studies. The purpose of these studies was to optimize tracer uptake in the SLNs to facilitate preoperative localization with MRI, rather than intraoperative detection.…”
mentioning
confidence: 99%
“…Mori et al developed a novel method for monitoring single cell dynamics of macrophages using a high tesla magnetic resonance imaging (MRl) system [3] [4]. It acquires time series sectional macrophage images with contrast using 11.7 T MRI.…”
Section: Introductionmentioning
confidence: 99%